Qualidade na formação de professores: os cursos de pedagogia 5 estrelas - Neves, Antônia Regina Gomes (Universidade do Vale do Rio dos Sinos, 2016)
This Master’s Thesis is a research about the discourses of the quality in Pedagogy’s Courses with the “stamp 5 stars” of Guia do Estudante. The aim was to investigate how the quality provided at Guia do Estudante interpolate these courses and which are the understandings about quality of teacher training developed for them. Investigated what the Guia has proposed to courses through of his evaluation and the mode the courses developed a teacher training consider qualified in Pedagogy’s Courses. The data of research was composed for a questionnaire answered for coordinators of Courses 5 stars, for forms send by Guia do Estudante for coordinators and for the profile of graduates to the same courses. The research used like analysis tool the concept of discursive practices of Michel Foucault. Was used the theorizations about teachers training, the studies about quality of teacher training and the Foucauldian studies. Analytically, it is possible to say that the understanding of quality that the Guia do Estudante moves is constituted in a neoliberal rationality and in a idea of performativity that has, in competition and ranking, central strategies of production to the quality’s imperative. Indicated that a course of Pedagogy that developed a teacher training performative and that shows the internationalization and the emphasis of the research’s act, can be considered, starting materials, a 5 stars courses. The formation that the courses developed has implications to the mode to be a teacher of the future pedagogues, this mode has some characteristics like developed learnings, act socially, articulate theoretical and practical knowledge and to have the teaching how the basis of actuation, this characteristics was looked how of the professional that I called of “5 stars pedagogue”. It’s not possible deny the productivity and the quality of this 5 stars courses, but it is important has clarity that the effects can be more exclusives that the promises that the quality’s imperative shows to the courses.
Keywords: Qualidade; Formação de professores; Curso de pedagogia; Guia do estudante; Quality; Teacher training; Pedagogy course; Guia do estudante; ACCNPQ::Ciências Humanas::Educação